Roles of MIWI, MILI and PLD6 in small RNA regulation in mouse growing oocytes. Issue 9 (23rd January 2017) - Kabayama, Yuka; Toh, Hidehiro; Katanaya, Ami; Sakurai, Takayuki; Chuma, Shinichiro; Kuramochi-Miyagawa, Satomi; Saga, Yumiko; Nakano, Toru; Sasaki, Hiroyuki
Abstract: The mouse PIWI-interacting RNA (piRNA) pathway produces a class of 26–30-nucleotide (nt) small RNAs and is essential for spermatogenesis and retrotransposon repression. In oocytes, however, its regulation and function are poorly understood. In the present study, we investigated the consequences of loss of piRNA-pathway components in growing oocytes. When MILI (or PIWIL2), a PIWI family member, was depleted by gene knockout, almost all piRNAs disappeared. This severe loss of piRNA was accompanied by an increase in transcripts derived from specific retrotransposons, especially IAPs. MIWI (or PIWIL1) depletion had a smaller effect. In oocytes lacking PLD6 (or ZUCCHINI or MITOPLD), a mitochondrial nuclease/phospholipase involved in piRNA biogenesis in male germ cells, the piRNA level was decreased to 50% compared to wild-type, a phenotype much milder than that in males. Since PLD6 is essential for the creation of the 5΄ ends of primary piRNAs in males, the presence of mature piRNA in PLD6-depleted oocytes suggests the presence of compensating enzymes. Furthermore, we identified novel 21–23-nt small RNAs, termed spiRNAs, possessing a 10-nt complementarity with piRNAs, which were produced dependent on MILI and independent of DICER. Our study revealed the differences in the biogenesis and function of the piRNA pathway between sexes.